The impact of labor migration and the attitudes towards family obligations among children of OFW's. - Monteclaro, Mikee Grace N
Thirty-five children of Overseas Filipino Workers were examined in this study regarding the impact of labor migration, their attitudes towards family obligations and the different issues that affect them. This research shows that children have a good state of well-being for they scored high in the self-esteem and sense of power scale. It was also found that children of OFWs especially females possessed stronger values and greater expectations regarding their duty to assist, respect and support their families. These findings suggest that children of OFWs were not greatly affected by the nature of work of their parents. Extended families play a major role in helping the child get through the emotional hardships they are facing.